2016
DOI: 10.2355/isijinternational.isijint-2015-567
|View full text |Cite
|
Sign up to set email alerts
|

Development of Recrystallization Texture in Severely Cold-rolled Pure Iron

Abstract: The mechanism of recrystallization texture development is changed by the chemical composition of materials, cold-rolling reduction, and annealing conditions. This study discusses the development of recrystallization texture for severely cold-rolled pure iron. In cold-rolled iron with 99.8% reduction, the deformation texture was a strong α-fiber (RD// < 011 > ) with high strain. During annealing in a temperature range from 20°C to 800°C, in this highly strained α-fiber, the microstructure started to recover fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
2
12
1
Order By: Relevance
“…1) In contrast, Gobernado et al explained the formation of recrystallization texture based on the oriented nucleation theory of recrystallization in a Fe-3.2mass%Si alloy that was cold-rolled at 95% reduction in which recrystallized grains with {311} < 136 > orientation preferentially nucleated in the deformed grains with {100} < 011 > orientation and recrystallization completed by their growth, 2) despite the fact that the deformed {100} < 011 > grains The effect of Si and Al additions on the recrystallization behavior of severely cold-rolled Fe by 99.8% reduction was investigated in comparison with a previous study on pure Fe. 6) In Fe-0.3mass%Si alloy, recrystallized grain with {411} < 011 > and {411} < 148 > preferentially nucleated at an early stage of recrystallization, and the texture did not changed substantially with the progress of recrystallization, which supports the oriented nucleation theory. The {411} < 148 > texture significantly increased at the expense of recrystallized grains with {100} < 023 > and ND// < 111 > during normal grain growth.…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…1) In contrast, Gobernado et al explained the formation of recrystallization texture based on the oriented nucleation theory of recrystallization in a Fe-3.2mass%Si alloy that was cold-rolled at 95% reduction in which recrystallized grains with {311} < 136 > orientation preferentially nucleated in the deformed grains with {100} < 011 > orientation and recrystallization completed by their growth, 2) despite the fact that the deformed {100} < 011 > grains The effect of Si and Al additions on the recrystallization behavior of severely cold-rolled Fe by 99.8% reduction was investigated in comparison with a previous study on pure Fe. 6) In Fe-0.3mass%Si alloy, recrystallized grain with {411} < 011 > and {411} < 148 > preferentially nucleated at an early stage of recrystallization, and the texture did not changed substantially with the progress of recrystallization, which supports the oriented nucleation theory. The {411} < 148 > texture significantly increased at the expense of recrystallized grains with {100} < 023 > and ND// < 111 > during normal grain growth.…”
Section: Introductionsupporting
confidence: 56%
“…1(b). Previous study of pure iron by the present authors, 6) revealed that α-fiber texture with the maximum intensity in {411} < 011 > developed after sever cold-rolling. Accordingly, a difference in severe cold-rolling texture between Fe-0.3mass%Si alloy and pure iron was recognized.…”
Section: Recrystallization Behavior In the Fe-03mass%sisupporting
confidence: 47%
See 3 more Smart Citations